Peran dan Urgensi Psikologi Pembelajaran Pendidikan Agama Islam - Nihaya, Musdalifah (CV. ULIL ALBAB CORP, 2024)
One of the materials contained in Islamic religious education books is a discussion of fasting. Fasting is the main worship which is defined as one of the pillars of Islam that must be done for a Muslim. Basically, fasting in the understanding of students tends to be limited by the terms and harmony in the learning process, while the nature of fasting in the form of appreciation and practice of the values of spirituality and morality gets less attention. So the purpose of this study is to determine the urgency of the development of Islamic Religious Education learning in teaching material